Effects of alkyl-ketene dimer on physical, mechanical and formaldehyde emission properties of particleboard produced with melamine-impregnated paper waste - Basboga, Ibrahim Halil; Basboga, Hulya Varlibas; Tasdemir, Cagatay; Atar, Ilkay; Yuce, Ozcan; Karademir, Arif; Mengeloglu, Fatih (Taylor & Francis Ltd, 2024)
This study aimed to enhance the physical properties and the weak heat transmission of the core layer, which are the weak points of particleboard produced using melamine-impregnated paper waste (MIPW) as an adhesive. Alkyl-ketene dimer (AKD) and paraffin were used as water-repellent chemicals. MIPW was used as an adhesive, and no additional resin was used. As a result of this study, the samples' physical properties improved with AKD and paraffin's existence. Moreover, it has been approved that AKD is more effective than paraffin in improving the physical properties of the particleboard because AKD improves ester bonding with hydroxyl groups of cellulose fibers. The usage of water repellents resulted in the improvement of internal bond (IB) properties. It was determined that the type and amount of water-repellent chemicals significantly affected the mechanical and physical properties and formaldehyde content of the produced particleboards, except for bending properties. Just the chemical type was found to be significantly effective on bending strength (BS) and modulus of elasticity (MOE) properties. Overall, the study findings suggested that AKD might be successfully utilized as a water-repellent chemical in particleboard manufacturing, while MIPWs used as an adhesive.
Keywords: Water-repellent; AKD; paraffin; heat transmission; wood-based composite